Hot air drying kinetics of thin layers of prickly pear fruit paste - Abraham-Juárez, Ma. del Rosario; Olalde-Portugal, Víctor; Cerón-García, Abel; Sosa-Morales, María Elena (Penerbit Universiti Kebangsaan Malaysia, 2019)
Hot air drying of thin layers of a paste from prickly pear fruit (without seeds) to obtain a chewy product was studied. The effect of air temperature (50 to 80°C) and sample thickness (4, 6, and 8 mm) on drying kinetics was analyzed. Drying curves were obtained, and drying data were fitted to Lewis, Henderson & Pabis, Peleg and Page mathematical models. The models were compared by two statistical parameters (coefficient of determination and reduced chi-squared). The drying rate curves showed that the layers of the paste were characterized by a single-falling-rate period. Water loss during drying was described by Fick’s equation and effective diffusivity, ranging between 0.75 and 7.05×10-9 m2s-1 depending on drying conditions. Activation energy was calculated from Arrhenius equation, being 34.51, 29.86, and 25.31 kJmol-1 for layers of 4, 6, and 8 mm thickness, respectively. The Page model fitted adequately the drying process of thin layers of the paste from prickly pear fruit.